The Escazu Agreement: challenges and opportunities for its implementation in Peru - Pinto-Bazurco Barandiarán, José Félix (2020)
The benefits of the implementation of a treaty are measured according to the capacity of a State to comply with its provisions effectively. The Regional Agreement on Access to Information, Public Participation and Access to Justice in MattersEnvironmental in Latin America and the Caribbean - known as the Escazú Agreement - regulates rights linked to human and environmental rights. Considering that many of the countries of the Latin American and Caribbean region subject their economic development to industries that are in direct conflict with the rights protected by the agreement, it is worth review whether your application can guarantee compliance with these rights without harming established economic processes. In order to support these ideas, this article will begin with a brief explanation of the content of the Escazú Agreement, to later study theapplication of the same from the point of view of international law, where the contingencies related to supranational jurisdiction, the implications regarding sovereignty, and the commitments and obligations that the States Parties would have to assume. Finally I know will address aspects related to the effect that its application will have in national law, such as are the possible changes in the legislation and the interpretative scope of some of its beginning.